2003
DOI: 10.1038/nrd1061
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the CREB pathway for memory enhancers

Abstract: Today, the clinical notion of 'memory disorder' is largely synonymous with 'Alzheimer's disease.' Only 50% of all dementias are of the Alzheimer's type though, and dementias represent only the more severe of all learning/memory disorders that derive from heredity, disease, injury or age. Perhaps as many as 30 million Americans suffer some type of clinically recognized memory disorder. To date, therapeutic drugs of only one class have been approved for the treatment of Alzheimer's disease. Fortunately, basic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
214
1
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 325 publications
(225 citation statements)
references
References 75 publications
8
214
1
2
Order By: Relevance
“…Evidence suggests that CREB activation is a critical step in the signaling cascade that initiates protein synthesis and the long-term morphological modifications that underlie LTP and long-term memory [29] . Consequently, agents that promote increases in the amounts or activity of CREB accelerate the process of long-term memory formation [30] . In the current study, PGS32 significantly increased the phosphorylation of CREB in primary hipppocampal neurons in as little as 4 min, as well as in mouse hippocampal regions after administration for a period of 10 days and participation in spatial learning tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that CREB activation is a critical step in the signaling cascade that initiates protein synthesis and the long-term morphological modifications that underlie LTP and long-term memory [29] . Consequently, agents that promote increases in the amounts or activity of CREB accelerate the process of long-term memory formation [30] . In the current study, PGS32 significantly increased the phosphorylation of CREB in primary hipppocampal neurons in as little as 4 min, as well as in mouse hippocampal regions after administration for a period of 10 days and participation in spatial learning tasks.…”
Section: Discussionmentioning
confidence: 99%
“…The transcription factor cAMP-response element binding protein (CREB) interacts with the cAMP-response element (CRE) in the promoter region of genes that encode proteins involved in the regulation of learning and memory (for reviews see [13,60]). A number of studies in a wide range of animal species have shown that CREB plays a key role in the formation of long-term memory (LTM) (for review see [88]). CREB is a constitutively nuclear protein whose activity is regulated by phosphorylation of both subunits of the homodimer [38].…”
Section: Fisetin Can Enhance Cognitive Functionmentioning
confidence: 99%
“…Recent studies analyze the mechanisms of drugs known as memory enhancers that appear to produce their results (thus far only in laboratory animals) through activation of a nuclear protein known as Cyclic-AMP Response Element Binding protein (CREB). Activated CREB is known to switch on genes in neural cells whose protein products strengthen synapses involved in long term memory (Hall, 2003;Tully et al, 2003). This enhancement of synaptic function is an essential component of learning.…”
Section: Neuro-cognitive Research On Learningmentioning
confidence: 99%